Extrapyramidal side effects induced by psychotropic, metoclopramide and l-noarg drugs with differential striatal fos family protein expression and nadph-diaphorase activity in dorsal and lateral striatum - Prieto, Sonia Carolina Guerrero (2021)
Coordenação de Aperfeiçoamento de Pessoal de Nivel Superior